2012
DOI: 10.1590/s1983-41952012000100006
|View full text |Cite
|
Sign up to set email alerts
|

The influence of low temperature on the evolution of concrete strength

Abstract: The mechanical strength of concrete can be affected by many conditions, among them the proportion of the mixture and the influence of external agents, such as external temperatures. Thus, the objective of the paper is to analyze the influence of low temperature on the evolution of concrete strength, from the molding of tests specimens cured at various temperatures. The specimens were submitted in the first 7 days, as curing temperatures ranging from 0°C to 25°C, simulating the lowest possible value for the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…According to the authors, when samples are molded and kept at low temperatures at early ages, there is no improvement in the hydration process, which may contribute to strength loss. However, Cecconello and Tutikan [39] studied the influence of low temperatures on concrete strength evolution and observed that concretes cured at lower temperatures at early ages could contribute to strength increase. The authors explain that the longer the hydration of Portland cement takes, the better the crystalline structure formation will be, thus clarifying that concretes cured at low temperatures at early ages can have a superior mechanical behavior than those cured at higher temperatures.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…According to the authors, when samples are molded and kept at low temperatures at early ages, there is no improvement in the hydration process, which may contribute to strength loss. However, Cecconello and Tutikan [39] studied the influence of low temperatures on concrete strength evolution and observed that concretes cured at lower temperatures at early ages could contribute to strength increase. The authors explain that the longer the hydration of Portland cement takes, the better the crystalline structure formation will be, thus clarifying that concretes cured at low temperatures at early ages can have a superior mechanical behavior than those cured at higher temperatures.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Many authors debate how temperature impacts strength gains and concrete hydration [4][5][6]. Studies show that compressive strength tends to be higher when the concrete is exposed to higher curing temperatures [7]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…When the mean ambient temperature is lower than +10 °C for at least three subsequent days, special requirements apply to the execution of concrete works. The temperature of +5 °C is regarded as the boundary temperature below which the concrete mix shall be protected from heat loss [ 1 , 2 , 3 , 4 , 5 , 6 ]. The literature describes numerous cases of doing works in such temperature conditions, including the cases showing negative effects of such operations [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%